Numeracy and Environmental Awareness Attitudes of Primary School-Age Children in the Malind Community - Ni Nyoman Rediani; Trinovianto G. R Hallatu; Ivylentine Datu Palittin; Hanova Rani E. Retnaningtyas; Herrio Tekdi Nainggolan; Sunarni Sunarni; Yus Witdarko; Yusri Yusri (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study examines students' numeracy abilities and attitudes toward environmental awareness among primary school-age children. Through an in-depth understanding of these two aspects, this study aims to provide a strong foundation for formulating appropriate solutions and learning methods that align with the needs and conditions of primary school-age children. Methodology: This research employed a descriptive method with a quantitative approach to explore numeracy literacy capabilities and attitudes toward environmental awareness. The descriptive research design was structured to provide detailed descriptions of the conditions or characteristics of the phenomena under study, focusing on "how" questions and presenting facts accurately and comprehensively. Main Findings: The results indicated that 57.5% of primary school-age children demonstrated moderate numeracy skills, while 32.5% fell into the poor category. This suggests the need for educational intervention to enhance numeracy capabilities. Additionally, children's environmental awareness attitudes largely fell into the good category at 65%. However, certain environmental awareness attitudes still require additional attention for optimal development. Systematic efforts remain necessary to improve both aspects. Novelty/Originality of this study: This study provides novel insights into numeracy capabilities and environmental awareness attitudes among primary school-age children from the Malind community in EswambiVillage. The data offers contextual and specific information regarding educational conditions and environmental awareness in this region, which has yet to be extensively studied in previous research.